Impact of offspring endothelial function from de novo hypertensive disorders during pregnancy: An evidence-based review - Abdull Sukor, Aslah Nabilah; Ankasha, Sheril June; Ugusman, Azizah; Aminuddin, Amilia; Mokhtar, Norfilza Mohd; Zainal Abidin, Shahidee; Ahmad, Mohd Faizal; Hamid, Adila A. (Frontiers in Surgery, 2022)
De novo hypertensive disorders of pregnancy (HDP) which consist of gestational hypertension and preeclampsia affect maternal and offspring morbidity and mortality, and potentially increase the risk of cardiovascular disease in the offspring. It is well known that de novo HDP causes various maternal complications, including cardiovascular diseases, placental abruption and liver and kidney failure. However, there are studies suggesting that offspring of pregnancies complicated by de novo HDP have an increased risk of long-term cardiovascular disease. The endothelium is an important regulator of vascular function, and its dysfunction is highly associated with the development of cardiovascular diseases. Hence, this review aimed to systematically identify articles related to the effect of de novo HDP on the endothelial function of the offspring. A computerized database search was conducted on PubMed, Scopus, and Medline from 1976 until 2022. A total of 685 articles were obtained. We identified another three additional articles through review articles and Google Scholar. Altogether, we used 13 articles for data extraction. All studies reported that endothelial function was impaired in the offspring of de novo HDP. This is most likely attributed to impaired vasodilation, subclinical atherosclerosis formation, inflammation, and dysregulated epigenetic regulation of endothelial functions.